THE ANALYSIS OF SCIENCE LEARNING SOURCES REVIEWED FROM THE META-COGNITIVE ABILITY OF THE VII GRADE THE STUDENTS OF SMP NEGERI 2 BOJA - Dewi, Novi Ratna; Wibowo, Sri Winda Agustina; Savitri, Erna Noor (Unnes Science Education Journal, 2017)
The object of learning in science was all natural objects that require in-depth exploration in learning. Media was needed to inform messages that had been designed by the educators so that learning was more realistic and fun. This study was designed with the research explorative type with qualitative descriptive approach, involving a teacher and the students in class VII at 2 different science classes at SMPN 2 Boja. The technique of data collection used documentation study and questionnaire. To test the validity of data and put confidence in the data validity criteria (credibility) used the triangulation. The result of study showed that the type of Science materials in general were in the form of teaching materials in print, visual and multimedia, nonetheless there had been no audiovisual Science teaching materials, for example the film. The teachers’ lack of knowledge about meta-cognitive made the meta-cognitive ability of the students was less good. The development of teaching materials had not narrowed to the achievement of specific competencies including meta-cognitive abilities of the students. It could be concluded that it was necessary to develop the type of teaching materials Audio Visual form of film in general often referred to as digital storytelling in science teaching to improve the students' meta-cognitive skills.